Differentiation of substance composition in the Typical Agrochernozems (Haplic Chernozems) of the Western Ukrainian Forest-Steppe - Papish, Ihor Y. (Journal of the Belarusian State University. Geography and Geology, 2017)
The study found in the Wet Atlantic facies of the Forest-Stepper Сhernozems of Ukraine soil formation leads to the vertical redistribution of Chernozem soil substance and formation of the mineral soil profile differentiated to varying degrees by carbonates, clay, and chemic-mineralogical composition. Haplic Сhernozems is characterized by the poorly differentiated profile by clay. The degree of vertical differentiation clay profile is directly proportional to the intensity of the processes of leaching and gleyzation. The whole complex of soil processes involved in the vertical redistribution of various clay phases has been identified using methods of chemical and mineralogical analyses. To the south-eastern direction the differentiation of the clay fraction in soil profile is changing from elluvio-accumulative type construction to poor accumulative once. In clay profiles of Haplic Agrochernozems the vertical redistribution of clay material is mainly due fraction smaller than 0.02 μm. The opposite character of profile distribution of mica-smectite and illite phases of clay minerals was discovered. Against the unbalanced losses of a part of clay plasma in the humus horizon the process of relative illitization was detected due to smectite eluviation and accumulation of illite, kaolinite and finely dispersed quartz.
Keywords: soil profile; Agrochernozems; carbonates; clay; smectite; illite